Development of a national consensus guideline for termination of resuscitation in the out-of-hospital environment. - Smyth, Michael A.; Brown, Terry P.; Fothergill, Rachael; Griffiths, Frances; Lall, Ranjit; Long, John; Petrou, Stavros; Siriwardena, Aloysius Niroshan; Slowther, Anne-Marie; Bettely, Lauren; Eli, Karin; Gardiner, Galina; et al. (British Paramedic Journal, 2026)
Introduction: Ambulance services in England attempted resuscitation in over 34,400 cases in 2022. Of these, 58% had the resuscitation attempt terminated at the scene and only 7.8% survived to hospital discharge. The decision to stop resuscitation is informed by a national guideline that is over 20 years old. This study describes the development of a revised termination of resuscitation (TOR) guideline. Methods: This was a mixed-methods study comprising a diagnostic test accuracy meta-analysis of TOR rules, modelling of multiple TOR rules using data from the Out-of-Hospital Cardiac Arrest Outcomes registry, a survey of ambulance services including a review of national policy documents, qualitative interviews with ambulance and emergency department (ED) clinicians, plus interviews with relatives of patients who did not survive a pre-hospital resuscitation attempt. These work packages informed a national consensus meeting with a wide range of stakeholders, employing nominal group techniques, to draft a revised TOR guideline. Results: The systematic review identified very low-certainty evidence from 43 studies, indicating that TOR rules are unlikely to be suitable for implementation in the UK. When we modelled the performance of TOR rules, the three best performing were the Marsden, KOCARC 1 and GOTO1 TOR rules. We identified considerable variation in practice across UK ambulance services; however, there was consistency across services with respect to perceived risks. Paramedics experienced tension when they felt that guidelines restricted them from acting in the patient's best interests. ED staff felt that paramedics should be empowered to stop resuscitation in some cases. Relatives felt that paramedics did a good job and that they had information that was useful for paramedics. Multiple stakeholders participated in a consensus conference to develop a revised TOR guideline. Conclusion: We iteratively derived updated TOR and verification of death guidelines.